Vibration Analysis of Narrow Tilting Three-Wheeled Vehicle Suspension System During Cornering - Maulana Syarif Habibi; Unggul Wasiwitono (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2018)
In Indonesia, there are a lot of vehicle on the road. These vehicles are used by the owner even there are only one or two passangers. That is the main reason of traffic jam in Indosia. However, motorbike is the best solution to fully use all part of the road that is provided in Indonesia because of its size, despite of motorbike has less safety than car. Therefore, combination between motorbike and car advantages have to be delivered through new type of vehicle which is narrow tilting three-wheeled vehicle. The goal that we want to achive from this final project is to test the vibration which affected the Narrow Tilting Three-Wheeled Vehicle (NTTWV). The condition that we analize is when the Narrow Tilting Three-Wheeled Vehicle (NTTWV) oscilliating during cornering. This condition is important because in Indonesia, there are a lot of hole located on the cornering part of the road. This is important in order to make the vehicle comfortable to be use in any condition. To have a better analysis, we use three variation which are suspension angle, spring constant and length of the arm. From the research, we could conclude that in order to feel less vibration acceleration we have to decrease the spring constant. Another way to lessen the vibration impact, we could lowering the suspension angle. Lastly, we could extend the arm length in order to have lower vibration impact.